Soft confectionery products: Quality parameters, interactions with processing and ingredients - Gunes, Recep; Palabiyik, Ibrahim; Konar, Nevzat; Toker, Omer Said (ELSEVIER SCI LTD, 2022)
The motivation in the preference of confectionery products consists of the perception formed during the purchase and consumption. This perception is a direct determining factor in the repeated purchasing behavior of the consumer. Also, the products must meet consumer demands. For this reason, it is very important to understand the confectionery quality characteristics, the factors affecting them, and their interaction with each other. In this context, the effects of major and minor components used in innovative soft confectionery products on quality should be considered first. As with all other foods, new ingredient(s) incorporated into the formulation and processing changes have significant effects on the quality characteristics of soft confectionery products. Therefore, in this review study, after giving information about soft confectionery products and their quality characteristics, the interactions of especially innovative components and processes that have important effects on these foods were discussed in detail.
Keywords: Quality; Soft confectionery; New ingredient; Processing; FLAVOR RELEASE; GUMMY CANDIES; AROMA RELEASE; MODEL SYSTEM; TEXTURE; GELATIN; SUGAR; PECTIN; STARCH; GELS; Chemistry; Food Science & Technology; Nutrition & Dietetics